Space-Time Estimates on Damped Fractional Wave Equation - Jiecheng Chen; Dashan Fan; Chunjie Zhang (Abstract and Applied Analysis)
We obtain space-time estimates on the solution u(t,x) to the Cauchy problem of damped fractional wave equation. We mainly focus on the linear equation. The almost everywhere convergence of the solution to linear equations as t→0+ is also studied, with the initial data satisfying certain regularity conditions.